Genotype-phenotype correlation in British families with X linked congenital stationary night blindness. Issue 11 (10th November 2003) - Allen, L E; Zito, I; Bradshaw, K; Patel, R J; Bird, A C; Fitzke, F; Yates, J R; Trump, D; Hardcastle, A J; Moore, A T
Abstract : Aim: To correlate the phenotype of X linked congenital stationary night blindness (CSNBX) with genotype. Methods: 11 CSNB families were diagnosed with the X linked form of the disease by clinical evaluation and mutation detection in either the NYX or CACNA1F gene . Phenotype of the CSNBX patients was defined by clinical examination, psychophysical, and standardised electrophysiological testing. Results: Comprehensive mutation screening identified NYX gene mutations in eight families and CACNA1F gene mutations in three families. Electrophysiological and psychophysical evidence of a functioning but impaired rod system was present in subjects from each genotype group, although the responses tended to be more severely affected in subjects with NYX gene mutations. Scotopic oscillatory potentials were absent in all subjects with NYX gene mutations while subnormal OFF responses were specific to subjects with CACNA1F gene mutations. Conclusions: NYX gene mutations were a more frequent cause of CSNBX than CACNA1F gene mutations in the 11 British families studied. As evidence of a functioning rod system was identified in the majority of subjects tested, the clinical phenotypes "complete" and "incomplete" do not correlate with genotype. Instead, electrophysiological indicators of inner retinal function, specifically the characteristics of scotopic oscillatory potentials, 30 Hz flicker and the OFF response, may prove more discriminatory.